Research on Hysteretic Behavior of Cold-Formed Thin-Wall Rolled Edge Channel Steel Flexural Members. Issue 1 (1st January 2022) - Yang, Jiabao; Guo, Yanli; Yu, Lipeng; Hu, Chengli; Liu, Yafei
Abstract: The finite element software ABAQUS is used to calculate and analyze the mechanical performance of cold-formed thin-walled curved channel steel members under horizontal reciprocating load. Double nonlinear finite element model needs to be considered, the influence of geometric imperfection and residual stress. The accuracy of the results was verified by comparing with the relevant test results. On the basis of controlling the main parameters such as width-thickness ratio, axial compression ratio, slenderness ratio and buckling mode, the numerical simulation results of 9 hysteretic specimens were selected to research the influence of the above factors on the hysteretic performance of the flexural members. The analysis results show that the width to thickness ratio, axial compression ratio and slenderness ratio have great influence on the hysteretic performance of the flexural members. The larger the three main parameters are, the worse the bearing capacity, ductility and energy consumption of the members will be. Therefore, the design should avoid as far as possible to choose a larger width-thickness ratio and slenderness ratio section components.